(untitled) (Fiep Bulletin - online, 2011)
The number of deaths due the coronary heart disease is increasingly growing every day. The Beginning of these diseases can happen for several reasons, one of them is obesity. Physical activities like Yoga and maintain healthy habits may be valid to prevent these diseases in our lives. The study aims to analyze the coronary heart risk of female federal civil servants yoga’s practicing and nom-practicing by WHR. We measured the waist and hip of 31 women, age group ranges from 29 to 61 years. The results show that the women that practice yoga have a lower risk of developing some type of heart disease compared with those women who do not practice this activity.